Comparison of outcome between sole operation and operation after tube thoracostomy in late phase empyema - Shao-Syuan Tong; Yi-Ling Chen; Ya-Fu Cheng; Ching-Yuan Cheng; Chang-Lun Huang; Wei-Heng Hung; Bing‑Yen Wang (Scientific Reports)
Abstract Empyema is a severe and potentially life-threatening condition characterized by infection in the pleural cavity with pus collection. Treatment options include antibiotics, tube thoracostomy, video-assisted thoracic surgery (VATS) decortication, or open thoracotomy. This study investigated whether decortication without pre-operative tube thoracostomy results in better outcomes for stage II and III empyema. We included 1042 patients with stage II or III empyema who underwent surgical decortication from January 2012 to December 2021. Among these patients, 713 underwent sole operation, and 329 underwent operation after tube thoracostomy. Patients were classified into two groups: sole operation (713 patients) and operation after tube thoracostomy (329 patients). Primary outcomes were peri-operative and in-hospital characteristics. Secondary outcomes analyzed 1-year overall survival rate and 1-year event-free survival. After 1:1 propensity score matching, 620 patients were included, with each group consisting of 310 patients. The sole operation group had significantly lower hospital mortality and 30-day re-intervention rates and shorter time between diagnosis and operation, operation time, ICU stay, ventilator duration, and hospital stay. The sole operation group also had higher 1-year overall survival and 1-year event-free survival. The first intervention for advanced-stage empyema is crucial. Even when patients ultimately require surgery, pre-operative tube thoracostomy could lead to poorer outcomes. Direct surgical management for stage II and III empyema is simpler and more effective.